2005
DOI: 10.1590/s1516-44462005000200009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of somatic symptoms on the performance of elders in the Beck Depression Inventory (BDI)

Abstract: Positive answers in the BDI Somatic and Performance subscale must be carefully assessed among elder subjects. The age factor, either by aging or due to several diseases, can bring signs that are not necessarily symptoms of major depression. Further studies are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
(2 reference statements)
0
16
0
4
Order By: Relevance
“…Although it is known that pulmonary rehabilitation may improve recognized predictors of mortality such as Wpeak, dyspnea, and quality of life, there is no evidence yet that pulmonary rehabilitation is beneficial with regard to survival. 46 Further observational studies of the correlates of depressive symptoms and their specific components such as hopelessness 47 or somatic complaints 48 are needed before proposing interventions. Finally, the assessment of depressive symptoms in our study was limited to a single point in time.…”
mentioning
confidence: 99%
“…Although it is known that pulmonary rehabilitation may improve recognized predictors of mortality such as Wpeak, dyspnea, and quality of life, there is no evidence yet that pulmonary rehabilitation is beneficial with regard to survival. 46 Further observational studies of the correlates of depressive symptoms and their specific components such as hopelessness 47 or somatic complaints 48 are needed before proposing interventions. Finally, the assessment of depressive symptoms in our study was limited to a single point in time.…”
mentioning
confidence: 99%
“…As there are worries that somatic symptoms of the postpartum could render a BDI screening inaccurate, the examination of its two factors in future studies is suggested. A similar recommendation has been made for the use of the BDI in the elderly [12]. Whether the presence of somatic symptoms should be disregarded, however, is unclear at this point.…”
Section: Discussionmentioning
confidence: 83%
“…This is in accordance with spontaneous hot flash disappearance 26 and age-related psychological worsening. 27 The latter may be related to the process of brain aging but also to worsening health and social contributing factors, such as retirement, loneliness, deaths of friends and relatives, and financial difficulties. As reported by other authors, BMI was associated with higher vasomotor [28][29][30][31] and mood 30 scores.…”
Section: Discussionmentioning
confidence: 99%